Attribution of illegitimate child's nasb to the biological father: analysis from the perspective of Malaysian law, muzakarah fatwa committee, state fatwas and maqasid aI-shariah - Aziz, Siti Noor Ain; Razaly, Mohamad Zaki; Othman, Norizan; Saja@Mearaj, Mahasin; Yaakob, Ahmad Nawawi; Md Nawi, Sofwah (UiTM Cawangan Johor, 2021)
A ruling by Malaysia s Court of Appeal in 2017 that Muslim children conceived out of wedlock can carry their fathers name has sparked a debate over the civil courts jurisdiction to set aside a fatwa. But this decision was overruled by Federal Court in 2019. This study aims to analyse the constitutional issues between statutory law and fatwa, followed by the analysis of whether the denial of the right to carry biological fathers name is in line with the Maqasid al-Shariah. This study was carried out using qualitative research method. The collection of data is derived from an unstructured interview with two experts in the field of constitutional law andfat.va. Secondary data analysis was obtained from National and state fatwas, legal documents, court cases, articles from the journal, book, and newspaper. This study concludes that whether the judgment is constitutional or unconstitutional depends on the interpretation made by the learned judges of the provisions in the Statutes. From the Maqasid al-Shariah point of view, Muslim scholars who disallow the ascription of paternity to the illegitimate children's biological father, uphold to preserve the purity of lineage (hiznasb), while the group who allows it chose to prevent harms and preserve dignity (hifz al-irdh). This study contributes by providing insights on the relevancy of illegitimate children s attribution in the constitution and Maqasid al-Shariah point of view.